1984
DOI: 10.1002/j.1460-2075.1984.tb01943.x
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus E1A protein activation of an integrated viral gene.

Abstract: Adenovirus early region 1A (E1A) protein stimulates transcription from five viral promoters during the early phase of infection. This protein also stimulates transcription from non‐viral genes which are newly introduced into cells by infection or transfection, but not from the endogenous copies of these non‐viral genes. Here we show that E1A protein induces expression of an early adenovirus gene integrated into the chromosomal DNA of stably transformed cells. This induction requires the continuous expression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1985
1985
1987
1987

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…The relative efficiency with which the ElA 13S and 12S products induce early viral gene transcription appears to vary greatly, depending on the experimental system or early gene analyzed. In several studies it has been concluded that the 12S mRNA product lacks transcription-inducing activity (4,11,18,37,51). In other cases the ElA 12S mRNA product was shown to induce adenovirus early gene transcription, but at levels somewhat reduced compared with those induced by the 13S mRNA product (10,40,58).…”
Section: Discussionmentioning
confidence: 99%
“…The relative efficiency with which the ElA 13S and 12S products induce early viral gene transcription appears to vary greatly, depending on the experimental system or early gene analyzed. In several studies it has been concluded that the 12S mRNA product lacks transcription-inducing activity (4,11,18,37,51). In other cases the ElA 12S mRNA product was shown to induce adenovirus early gene transcription, but at levels somewhat reduced compared with those induced by the 13S mRNA product (10,40,58).…”
Section: Discussionmentioning
confidence: 99%
“…The EIA protein can activate expression of endogenous cellular genes (Stein and Ziff, 1984;Rosenthal et al, 1985) and transferred viral genes (Curtois and Berk, 1984). The EIA protein can also have a negative regulatory effect by repressing enhancerinduced stimulation of transcription (Borelli et al, 1984;Velcich and Ziff, 1985).…”
Section: Possible Influence Of Eia Enhancer On Expressionmentioning
confidence: 99%
“…Therefore, the ability of HSV to activate transcription from viral, but not cellular, genes in the host genome apparently contrasts with the general activation of both viral and cellular promoters resident in a plasmid. The activation of integrated viral genes in adenovirus-transformed cells during subsequent adenovirus infection has been cited as a demonstration of specificity of IE gene product activation, and that this specificity is absent, or masked, during short-term transfection assays (Curtois and Berk, 1984). However, it is possible that integration of foreign genes into the cellular genome during biochemical transformation occurs at locations which are particularly accessible to IE gene product activation.…”
Section: Introductionmentioning
confidence: 99%